2008
DOI: 10.4319/lo.2008.53.5.1784
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between inorganic iron and cadmium uptake in the marine diatom Thalassiosira oceanica

Abstract: We examined substrate-saturated Fe(II) vs. Fe(III) uptake rates of Thalassiosira oceanica preconditioned to varying degrees of Fe limitation. Inorganic Fe(III) uptake rates by Fe-sufficient T. oceanica were 2.4-fold faster than the corresponding inorganic Fe(II) uptake rates. However, when cultures were severely Fe limited, the rate of Fe(II) uptake was upregulated 15-fold, while that of Fe(III) uptake increased only fivefold. The interactions between substrate-saturated uptake rates of inorganic Cd(II) and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 32 publications
5
61
0
2
Order By: Relevance
“…Culturing experiments have demonstrated that the uptake of Cd into plankton-as with other divalent metalsoccurs in direct proportion to dissolved [Cd 2+ ], although this pattern can be modulated by competition with the availability of other metals (19,20). For example, Zn limitation has been shown to increase Cd uptake in bacteria (21) and phytoplankton (22)(23)(24), with Fe restriction also promoting an increase in cellular Cd quotas in culture (24,25). Cd is imported by a wide range of microorganisms as they accumulate geochemically similar trace elements for physiological use (26), thereby removing Cd from seawater.…”
Section: Discussionmentioning
confidence: 99%
“…Culturing experiments have demonstrated that the uptake of Cd into plankton-as with other divalent metalsoccurs in direct proportion to dissolved [Cd 2+ ], although this pattern can be modulated by competition with the availability of other metals (19,20). For example, Zn limitation has been shown to increase Cd uptake in bacteria (21) and phytoplankton (22)(23)(24), with Fe restriction also promoting an increase in cellular Cd quotas in culture (24,25). Cd is imported by a wide range of microorganisms as they accumulate geochemically similar trace elements for physiological use (26), thereby removing Cd from seawater.…”
Section: Discussionmentioning
confidence: 99%
“…This process is described as a growth rate dilution effect, where phosphate uptake is more sensitive to growth rate than metal uptake. A recent study provided an additional biochemical mechanism for this phenomenon where iron limitation of a diatom was found to cause an upregulation of ferrous iron transporters, which concurrently resulted in increased transport of other divalent cations such as cadmium (Lane et al, 2008). Both the Zn depletion and Fe limitation mechanisms result in increased Cd:P ratios in phytoplankton that in turn should deplete dissolved Cd relative to P in the upper water column with export and remineralization of particulate material below the euphotic zone.…”
Section: Ecological Stoichiometry Of Cobalt Inferred From Correlationmentioning
confidence: 99%
“…Sunda and Huntsman, 1995;Saito et al, 2004;Noble et al, 2008), implying the importance of micronutrient processes over earlier suggestions that atmospheric input and scavenging processes dominate the oceanic distribution of cobalt (Whitfield and Turner, 1987). Yet explanations for these linear metal:macronutrient relationships and, in particular, apparent "kinks" in these linear relationships (Boyle et al, 1981;Boyle, 1988;Hunter, 1992, 1995;Saager and de Baar, 1993;de Baar et al, 1994;Cullen, 2006), have arguably not reached a consensus due to the presence of multiple processes and subtle complexities such as: (1) limited knowledge of the underlying biochemistries; (2) the influence of iron deficiency, which depresses phytoplankton growth rate but not metal uptake, resulting in changes in metal:P ratios through a process called growth rate dilution (Sunda and Huntsman, 2000;Cullen et al, 2003;Cullen, 2006;Lane et al, 2009), as well as causing upregulation of ferrous iron transporters that also transport other divalent cations (Lane et al, 2008); (3) biochemical substitution of Zn, Cd, or Co, for example, in the active sites of metalloenzymes (Morel et al, 1994; al., 2008); and (4) the role of organic ligands in controlling metal bioavailability (Bruland and Lohan, 2003). These issues will be discussed below in the context of our Ross Sea data.…”
Section: Ecological Stoichiometry Of Cobalt Inferred From Correlationmentioning
confidence: 99%
“…Les expériences de cinétique de prise en charge du Cd à court terme (et quelques expériences à long terme) chez diverses espèces phytoplanctoniques suggèrent que ce métal peut être accumulé par les transporteurs de différents micronutriments, soit les transporteurs de Mn (HART et al, 1979;SUNDA et HUNTSMAN, 1996, 1998a, de Zn de haute affinité (LAVOIE et al, 2012a;SUNDA et HUNTSMAN, 1998a;TÖPPERWIEN et al, 2007a, 2007b (LANE et al, 2008(LANE et al, , 2009 (SUNDA et HUNTSMAN, 1996, 1998a Ainsi, la régulation de la synthèse de transporteurs de métaux essentiels (ex. : du Zn et du Mn) par rétroaction négative en réponse à la variation des concentrations de ces cations essentiels affectera la biodisponibilité du Cd et sa toxicité à long terme.…”
Section: Régulation De L'accumulation Des Métaux Essentiels Et Impactunclassified
“…Chez cette dernière espèce, le Fe(III) ne jouerait pas de rôle antagoniste sur l'accumulation de Cd pour une exposition de moins d'une heure (C. HOANG, communication personnelle) ou une exposition de 60 h (LAVOIE et al, 2012b). Il est possible que le rôle antagoniste du Fe(III) sur la prise en charge et la toxicité du Cd chez certaines espèces d'algues unicellulaires soit lié à la synthèse/dégradation de transporteurs de Fe(II) (pouvant transporter le Cd par inadvertance) comme il a été suggéré chez les plantes supérieures (COHEN et al, 1998;THOMINE et al, 2000) ainsi que chez une espèce de diatomée marine (LANE et al, 2008(LANE et al, , 2009). …”
Section: Régulation De L'accumulation Des Métaux Essentiels Et Impactunclassified